2022
DOI: 10.1101/2022.11.27.518126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intraspecific variation of transposable elements reveals differences in the evolutionary history of fungal phytopathogen pathotypes

Abstract: Fungal plant pathogens pose a significant threat to biodiversity and food security worldwide. This threat is aggravated by their rapidly evolving genomes that adapt to evade host plant defenses, reducing the efficacy of deployed resistant crops.Magnaporthe oryzaeinfects rice, wheat, and many other grasses, resulting in significant crop losses each year. Transposable elements (TEs) are hypothesized to be involved in the evolution and rapid adaptation ofM. oryzae. However, there is still much to understand about… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 84 publications
1
3
0
Order By: Relevance
“…A previous report has shown that MoO has a much greater TE content than MoT [20]. Therefore, given this result and the greatly increased number of PAV orthogroups in MoT compared to MoO we observed (Fig.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…A previous report has shown that MoO has a much greater TE content than MoT [20]. Therefore, given this result and the greatly increased number of PAV orthogroups in MoT compared to MoO we observed (Fig.…”
Section: Resultssupporting
confidence: 64%
“…The two M. oryzae pathotypes share some major differences in their TE content [20] and very different life histories, with MoO originating 9,800 thousand years ago [17] and propagating mostly clonally since then, while MoT is thought to have emerged approximately 60 years ago from a multi-hybrid swarm of many different M. oryzae pathotypes [12,16]. We propose that the differences in PAV across the two pathotypes may reflect these life histories, with MoO exhibiting more of a stable equilibrium and much slower paced evolution, where PAV events happen in specifically defined compartments of the genome, while MoT is rapidly losing and gaining genes, even in areas of the genome where most of the conserved genes in MoO are located.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated genetic elements contribute to genome plasticity in P. oryzae . The content in transposable elements and repeat sequences in P. oryzae genomes varies between 5% and 11%, which is moderate for phytopathogenic ascomycetes (Chiapello et al., 2015; Dean et al., 2005; Nakamoto et al., 2023). Genes that show presence/absence polymorphism between lineages are frequently associated with transposable elements, suggesting that transposons are implicated in their acquisition and/or loss (Yoshida et al., 2016).…”
Section: Genomicsmentioning
confidence: 99%